Um estudo exploratório sobre as práticas socio-ambientais de empresas multinacionales no setor de mineração do Peru - Bellido Ordoñez, Natalí (2005)
The present work evaluates the environmental practices in the sector of the greater metallic mining industry of Peru. This sector this dominated by the presence of transnational companies. These transnational companies are regulated by two different realities of environmental norms. The first is composed the corporate norms where the companies' headquarters are located. The second reality is the regulation by the country where the subsidiary is located, in this case Peru. These are two very discordant realities. With the internationalization of environmental concerns, due importance must be given to Corporate Social Responsibility. This is because transnational companies need to maintain an international image. This image can be vulnerable to negative critiques in case of heterogeneity, since the companies' environmental standards must be the same as the rest of the world. Peru does not have a Department of Environment. Nevertheless there exists a National Council of the Environment (CONAM). This is a decentralized public organization, assigned to the area of the Presidency of the Ministers' Council. In this case study, two transnational companies of the greater peruvian mining industry are analyzed. The no existence of public policies in the social realm is observed. Because of this, the conclusions of this study are orientated towards fomenting the creation and application of public policies for two socio-environmental problems: first, the generation of secondary employment, and second, recovery of the environmental liabilities.